Refinement of high-risk endometrial cancer classification using DNA damage response biomarkers: a TransPORTEC initiative. (December 2018) - Auguste, Aurélie; Genestie, Catherine; Bruyn, Marco; Adam, Julien; Formal, Audrey; Drusch, Françoise; Pautier, Patricia; Crosbie, Emma; MacKay, Helen; Kitchener, Henry; Powell, Melanie; Pollock, Pamela; et al.
Abstract TheTrans PORTEC consortium previouslclassified high-risk endometrial cancer including poor-risk histologies such as clear cells, into four molecular subtypes "POLE mutated, " "microsatellite unstable, " "TP53 mutated, " and "no specific molecular profile." We evaluated whether DNA damage response biomarkers could further refine this high-risk tumors classification, in particular the heterogeneous "no specific molecular profile" and "TP53 mutated" subsets recently qualified as poor prognosis in high-risk endometrial cancer. DNA damage response biomarkers including proteins involved in DNA damage (δ-H2AX), homologous recombination (RAD51), regulators of error-prone Non Homologous End-Joining (DNA-pk, FANCD2), and PARP-1 were evaluated in 116 high-risk tumors by immunohistochemistry. CD8 and PD-1 expression by immunochemistry and mutation analyses were performed previously. Survival outcome were calculated using Kaplan-Meier and Log-rank test. None of the DNA damage response biomarkers alone were prognostic. However markers were informative within molecular subsets. Among the "no specific molecular profile" subset, δ-H2AX+ was significantly predictive of poor disease free survival (Hazard Ratio = 2.56;p  = 0.026), and among "TP53 mutated, " a DNA-pk+/FANCD2- profile (favouring error-prone Non Homologous End-Joining) predicted worst disease free survival (Hazard Ratio = 4.95;p  = 0.009) resulting in five distinct prognostic subgroups from best to worst prognosis: group1 "POLE mutated/Microsatellite unstable" > group2 "no specific molecular profile with no DNA damage" > group3 "TP53 mutated/Non Homologous End-Joining negative" > group4 "no specific molecular profile with high DNA damage" > group5 "TP53 mutated/Non Homologous End-Joining positive";p  = 0.0002). Actionable targets were also different among subsets. Group3 had significantly higher infiltration of PD-1+ immune cells (p  = 0.003), segregating with group1. Group2 had frequent PI3K pathway mutations and ER positivity. While group5, with the worst prognosis, had high DNA damage and PARP-1 expression providing a rationale for PARP inhibition. Our findings have refined theTrans PORTEC prognostic classification of high-risk endometrial cancer into five distinct subgroups by integrating DNA damage response biomarkers and identified molecular subtype-specific therapeutic strategies.